HISTOMORPHOMETRY OF SEMINIFEROUS TUBULES OF LOCAL GOATS FIXED WITH DIFFERENT FIXATIVES - Fitriani Fitriani; Sri Wahyuni; Muslim Akmal; Dasrul Dasrul; Cut Dahlia Iskandar (Jurnal Kedokteran Hewan, 2018)
The aim of this study was to further understand the histomorphometry of seminiferous tubules from local goat testicles that were fixed with different fixatives. Nine testicles were randomly chosen, each fixed with 10% formalin, 10% neutral buffered formalin (NBF), and 4% paraformaldehyde (PFA) solutions. The sample was then proceeded to histology preparation and stained with haematoxylin eosin (HE). Observation of the tissue was carried out using microscope and the data obtained was analyzed statistically. The results showed that there was a significant difference (P0.05) on each fixative in tubular diameter and membrane, and very significant difference (P0.01) on germinal cell and staining absorbability. Duncan test result on tubular diameter showed that the use of PFA fixative was significantly different (P0.05) compared to formalin fixative while the use of NBF fixative had no significant difference (P0.05) compared to PFA fixative. In addition, the measurement of interstitial membrane of seminiferous tubules showed no significant difference (P0.05) among three fixatives. To conclude, formalin, NBF, and PFA fixatives affect seminiferous tubules, basal membrane structure, and germinal cell appearance inside tubular lumen. Type of tissues and fixative must be considered in selecting the suitable fixative.